615 A pilot study to implement the Type 1 & 2 SLE Model into clinical care. (14th December 2022) - Eudy, Amanda M; Rogers, Jennifer L; Sun, Kai; Sadun, Rebecca E; Pisetsky, David S; Maheswaranathan, Mithu; Doss, Jayanth; Criscione-Schreiber, Lisa G; Clowse, Megan EB
Abstract : Background: The Type 1 & 2 SLE Model was developed to better explain the signs, symptoms, and management goals of systemic lupus erythematosus (SLE) to patients. We assembled tools to discuss the Type 1 & 2 SLE Model, collectively called SLE@Duke, including patient-reported outcome (PRO) measures, physician global assessments (PGAs) for Type 1 and 2 SLE activity, and a patient handout. In this pilot study, we aimed to implement SLE@Duke into rheumatology care with the goal of increasing the frequency of discussion of the Type 1 & 2 SLE Model. Methods: We conducted a 4-week study in Duke Rheumatology Clinics. Providers received training on SLE@Duke that reviewed each of the tools, summarized approaches to treating Type 2 SLE, and scored case examples of PGAs. During the intervention period, patients with SLE received a questionnaire at check-in that included the Systemic Lupus Activity Questionnaire and the American College of Rheumatology Fibromyalgia Severity Score. After each visit, patients completed an anonymous satisfaction survey. Providers completed baseline and follow-up surveys on their satisfaction with care and acceptability, appropriateness, and feasibility of SLE@Duke. Clinic notes of patients seen during the intervention period and 4-weeks prior to the intervention were reviewed. Providers were invited to participate in interviews about their experience after the intervention period. Results: Sixteen of 25 eligible providers participated (3 APPs, 8 faculty, 5 fellows); 67 patients with SLE were seen (36 pre-intervention and 31 intervention). At follow-up, provider surveys showed high scores for acceptability (4.0/5), appropriateness (4.15/5), and feasibility (4.2/5) of SLE@Duke (table 1). All providers agreed or completely agreed the intervention seemed possible; there was an increase in the proportion who felt the intervention was easy to use (50% to 83%). Type 1 & Type 2 PGAs were documented in 87% of notes. The discussion of Type 2 SLE symptoms increased from 44% to 74% of patients (p=0.02). Importantly, there was not an increase in the duration of clinic visits during the intervention period (table 2). Among 49 patients who completed surveys, satisfaction with care remained high (table 3). In interviews, most providers found SLE@Duke helpful to guide conversations and validate patients' feelings. Suggestions to improve SLE@Duke included a shortened PRO measure, more training on scoring PGAs, a referral network for Type 2 SLE symptom management, and more resources for patients and providers about Type 1 & 2 SLE. Conclusion: Through SLE@Duke, our general rheumatologists increased their discussion of Type 2 SLE symptoms without significantly increasing the duration of clinic visits. All patients remained highly satisfied with their care. Future work will take this intervention to other rheumatology clinics to determine its impact on patient outcomes. Trial Registration: NCT05426902 Lay Summary: In this pilot study, we assembled tools to discuss the Type 1 & 2 SLE Model, collectively called SLE@Duke. By implementing the Type 1 & 2 SLE Model, our general rheumatologists increased their discussion of Type 2 SLE symptoms without significantly increasing the duration of clinic visits. All patients remained highly satisfied with their care.